In-situ generated magnesium borohydride composite hydrogen storage material as well as preparation method and application thereof
By using two-dimensional materials such as graphene as support in magnesium borohydride hydrogen storage materials, synthesis of magnesium borohydride composite materials through intercalation-in-situ growth method, the problems of unstable hydrolysis reaction and high cost are solved, and high hydrogen yield is achieved The amount and controllable hydrolysis reaction are suitable for fuel cell hydrogen supply systems.
Patent Information
- Application Number
- CN202411272632.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The existing magnesium borohydride hydrogen storage materials are unstable in the hydrolysis reaction and are prone to react with air and water, resulting in too fast heat release and high cost, making it difficult to meet the needs of clean renewable hydrogen production.
Two-dimensional materials such as graphene, graphene oxide, MXene, silica, sepiolite, elolite and montmorillonite are used as carriers to synthesize magnesium borohydride composites through intercalation-in-situ growth method to form a stable limit. Domain framework, regulates hydrolysis reaction rate and hydrogen production performance.
It realizes high hydrogen yield and controllable hydrolysis reactions, which are suitable for fuel cell hydrogen supply systems, reduces the hydrolysis rate and cost of the material, and improves the stability and load efficiency of the material.
Smart Images

Figure CN119118059A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid-state hydrogen storage, and in particular to an in-situ generated magnesium borohydride composite hydrogen storage material and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has great potential in large-scale renewable clean energy integration and carbon emission reduction due to its diverse sources, high mass energy density, and non-polluting nature. However, the lack of safe, efficient, and inexpensive hydrogen production / storage technology has hindered the large-scale application of hydrogen energy. So far, clean, renewable hydrogen production methods and reversible hydrogen storage systems that meet the goals set by the U.S. Department of Energy (DOE) remain extremely challenging for materials science. Storing in solid-state media is one of the most efficient and safe ways to use hydrogen widely in the future. Among them, light metal borohydrides have attracted widespread attention due to their extremely high hydrogen storage capacity. For example, magnesium borohydride has an extremely high mass density (14.9wt%) and volume hydrogen storage density (145-147kg / m 3 ).
[0003] Although Mg(BH4)2 has the above advantages, it is unstable and easily reacts with oxygen and water vapor in the air. At the same time, the byproduct Mg(BO2)2 in the hydrolysis process easily adheres to the surface of Mg(BH4)2 to form a passivation layer, which seriously hinders the adsorption of water and the gas diffusion process. Theoretically, Mg(BH4)2 can release 3630mL / g of hydrogen in the hydrolysis reaction. However, too fast a hydrolysis reaction will release a lot of heat, which makes it unsuitable for portable applications.
[0004] Chinese patent document CN117550550A (patent number 202311518762.6) discloses a borohydride / graphene composite hydrogen storage material, a preparation method thereof, and its application in the field of hydrogen storage. By introducing graphene as a carrier, low hydrogen release starting and peak temperatures and good reversible hydrogen absorption and desorption performance during the borohydride hydrogen absorption and desorption cycle are finally achieved. However, the mass ratio of the carrier material to the borohydride described in the invention is 1:1 to 2, which is not conducive to cost savings and hinders actual production. In addition, the concept of the invention is to nano-confine the borohydride based on a two-dimensional planar structure to prepare a hydrogen storage material with hydrogen absorption and desorption cycle stability, which is different from the inventive concept of the present invention.
[0005] Chinese patent document CN115159451A (patent number 202210933325.X) discloses a method for preparing aluminum hydride / magnesium borohydride @MXene composite hydrogen storage material. By adjusting the interlayer spacing of the MXene material and liquid phase ball milling, the nanocomposite material is efficiently embedded in the MXene layered structure, solving the problem of poor confinement effect of nano-confined materials. However, the liquid phase ball milling method not only damages the two-dimensional material MXene, but also the confinement effect needs to be improved, which limits its further application.
[0006] Chinese patent document CN108609581A (patent number 201810513261.1) discloses a method for improving the antioxidant properties of magnesium borohydride and regulating its hydrolysis hydrogen production rate. By compounding magnesium borohydride with an ammonia source, the antioxidant property is improved. At the same time, the amount of NH3 in the ammonia compound is adjusted to achieve the regulation of the rate of hydrogen production by hydrolysis of magnesium borohydride. However, with the introduction of NH3, the gas purity is affected and the total amount of hydrogen produced is also greatly reduced.
[0007] In order to deal with the above problems, the use of two-dimensional materials as carriers is a breakthrough direction for the preparation of high performance and moderate hydrolysis rate. Among them, graphene, titanium carbide, silicon dioxide, sepiolite, halloysite and montmorillonite have the advantages of high surface area, adjustable functional groups (such as hydroxyl, carboxyl, epoxide, amino), porous microstructure, high thermal stability, and significant stability under strong acid and strong base conditions. They can increase the hydrogen evolution sites in the hydrolysis process of the material, improve stability, and act as a confined framework to reduce the hydrolysis rate of the material. At the same time, the unique intercalation-in situ growth method will enhance the interaction between magnesium borohydride and the carrier to further improve the loading efficiency and confinement effect. Current studies have shown that using the above materials as carriers has a certain positive effect on improving hydrogen release performance and regulating hydrolysis rate. Summary of the invention
[0008] In view of this, in order to solve the above-mentioned technical problems, the purpose of the present invention is to propose a preparation method and application of an in-situ generated magnesium borohydride composite hydrogen storage material. The hydrogen storage material prepared by the present invention has good hydrogen production performance and moderate reaction rate. The in-situ synthesized hydrogen storage material is based on the carrier as a stable confined framework and a high specific surface area. It has more hydrogen production sites and slower hydrogen production kinetics during the hydrolysis process, which can meet the needs of the hydrogen supply end of the fuel cell and can effectively alleviate the global energy crisis and environmental pollution problems.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first object of the present invention is to provide a method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material, which comprises the following steps:
[0011] S1. Add the support to the (CH3)2S·BH3 toluene solution in a glove box filled with Ar, and stir the mixture to obtain a suspension A;
[0012] S2. Weigh the suspension A and Mg(C4H9)2 heptane solution, stir until the reaction is complete to obtain a precipitate B, wash with anhydrous toluene solution and collect the precipitate B;
[0013] S3. The precipitate B is transferred to a vacuum drying oven and thermally decomposed under vacuum conditions to obtain the in-situ generated magnesium borohydride composite hydrogen storage material.
[0014] Furthermore, in step S1, the carrier is one or more of graphene, graphene oxide, MXene, silica, sepiolite, halloysite and montmorillonite.
[0015] Furthermore, in step S1, the stirring time is 15 to 30 minutes.
[0016] Furthermore, in step S1, the amount of carrier added is 3 to 50 mg, and the concentration of the (CH3)2S·BH3 toluene solution is 1 to 2M.
[0017] Furthermore, in step S2, the stirring time is 90 to 150 minutes.
[0018] Furthermore, in step S2, the concentration of Mg(C4H9)2 heptane is 1-2M, and the volume ratio of (CH3)2S·BH3 toluene solution to Mg(C4H9)2 heptane solution is (1.6-2):1.
[0019] Furthermore, in step S2, the volume of the anhydrous toluene solution is 10 to 15 mL, and the number of washing times is 3 to 5 times.
[0020] Furthermore, in step S3, the thermal decomposition is carried out under vacuum conditions, wherein the vacuum pressure is 2-4 Torr, the heating temperature is 75-90° C., and the heating time is 8-20 h.
[0021] The second object of the present invention is to protect the in-situ generated magnesium borohydride composite hydrogen storage material obtained by the above preparation method.
[0022] The third object of the present invention is to protect the application of the above-mentioned in-situ generated magnesium borohydride composite hydrogen storage material in hydrolysis hydrogen production. The hydrolysis hydrogen production material prepared by the present invention undergoes a hydrolysis reaction in pure water, the hydrolysis kinetics is fast and controllable, and the hydrogen release amount is high.
[0023] The beneficial effects of the present invention are:
[0024] The in-situ generated magnesium borohydride composite hydrogen storage material prepared by the present invention has good hydrogen production performance and moderate hydrolysis reaction rate. Among them, graphene, graphene oxide (GO), MXene, silicon dioxide, sepiolite, halloysite and / or montmorillonite have the advantages of high surface area, adjustable functional groups (such as hydroxyl, carboxyl, epoxide, amino), porous microstructure, high thermal stability, significant stability under strong acid and strong base conditions, etc., which can increase the hydrogen evolution site of the material hydrolysis process, improve stability, and reduce the material hydrolysis rate as a confined framework. At the same time, the unique intercalation-in-situ growth method will enhance the interaction between magnesium borohydride and the carrier to further improve the load efficiency and confinement effect. These characteristics make the hydrogen storage material of the present invention particularly suitable for the hydrogen supply system of fuel cells, with significant industrial application potential and market competitiveness.
[0025] In the prior art, α-Mg(BH4)2 and β-Mg(BH4)2 have been explored for use in hydrolysis to produce hydrogen, but research on the hydrolysis of γ-Mg(BH4)2, which has a higher hydrogen storage potential, has not been taken seriously. The present invention synthesizes high-purity γ-Mg(BH4)2 and loads it in situ on the surface of a carrier. The obtained composite material is subjected to hydrolysis to produce hydrogen. The hydrolysis reaction can occur at room temperature and different amounts of hydrogen are released. The hydrogen production is high and the hydrogen production rate is controllable. Compared with direct hydrolysis, it is more conducive to application in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD spectra of MBH, MBH@5GO, MBH@10GO and MBH@15GO hydrogen storage materials in Examples 1 to 3;
[0027] Figure 2 The kinetic curves of the hydrolysis of MBH, MBH@5GO, MBH@10GO, and MBH@15GO hydrogen storage materials in deionized water in Examples 1 to 3;
[0028] Figure 3 This is the SEM image of the MBH@10GO hydrogen storage material in Example 2;
[0029] Figure 4 XRD spectra of MBH, MBH@10MX, MBH@20MX, and MBH@30MX hydrogen storage materials in Examples 4 to 6;
[0030] Figure 5 The kinetic curves of the hydrolysis of MBH, MBH@10MX, MBH@20MX, and MBH@30MX hydrogen storage materials in deionized water in Examples 4 to 6;
[0031] Figure 6 This is the SEM image of the MBH@20MX hydrogen storage material in Example 5. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] The method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material of this embodiment comprises the following steps:
[0035] First, 5 mg of GO was added to 20 mL of 2M (CH3)2S·BH3 toluene solution in an Ar-filled glove box, and the mixture was stirred for 30 min by a magnetic stirrer. Subsequently, 10 mL of 1M Mg(C4H9)2 heptane solution was slowly added to the GO / (CH3)2S·BH3 mixed solution through a pressure-separating funnel and stirred vigorously for 120 min. After the reaction was completed, it was washed 4 times with 15 mL of anhydrous toluene and the formed gray precipitate was collected. Finally, it was transferred to a vacuum drying oven and dried at 80 ° C for 16 h under 3 Torr vacuum.
[0036] The XRD spectrum of the hydrogen storage material prepared by the above method is as follows: Figure 1 As shown, diffraction peaks corresponding to γ-Mg(BH4)2 appeared at 13.4°, 15.5°, 20.6°, 24.7°, etc. in the curve, indicating that the magnesium borohydride composite material was successfully synthesized by the intercalation-in situ growth method.
[0037] Figure 2 The hydrolysis kinetic curve of magnesium borohydride composite material at 25℃ is shown in Figure 2. Figure 2 It can be seen that 1g of powder can release 865mL of hydrogen within 6min. Compared with γ-Mg(BH4)2, the hydrolysis reaction of MBH@5GO is more controllable and milder, the hydrolysis rate is slower, and it still has a higher hydrogen production.
[0038] Example 2
[0039] The method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material of this embodiment comprises the following steps:
[0040] First, 10 mg of GO was added to 18 mL of 2M (CH3)2S·BH3 toluene solution in an Ar-filled glove box, and the mixture was stirred for 20 min by a magnetic stirrer. Subsequently, 10 mL of 1M Mg(C4H9)2 heptane solution was slowly added to the GO / (CH3)2S·BH3 mixed solution through a pressure funnel and stirred vigorously for 140 min. After the reaction was completed, it was washed three times with 12 mL of anhydrous toluene and the formed gray precipitate was collected. Finally, it was transferred to a vacuum drying oven and dried at 85 ° C for 12 h under 2 Torr vacuum.
[0041] The XRD spectrum of the hydrogen storage material prepared by the above method is as follows: Figure 1 As shown, diffraction peaks corresponding to γ-Mg(BH4)2 appeared at 13.4°, 15.5°, 20.6°, 24.7°, etc. in the curve, indicating that the magnesium borohydride composite material was successfully synthesized by the intercalation-in situ growth method.
[0042] Figure 2 The hydrolysis kinetic curve of magnesium borohydride composite material at 25℃ is shown in Figure 2. Figure 2 It can be seen that 1g powder can release 1300mL of hydrogen within 4min. Compared with γ-Mg(BH4)2, the hydrolysis reaction of MBH@10GO is more controllable and milder, the hydrolysis rate is slower, and it has a higher hydrogen production than γ-Mg(BH4)2.
[0043] from Figure 3 It can be seen that γ-Mg(BH4)2 is dispersed on the surface of GO, which effectively avoids the aggregation problem in the process of synthesizing Mg(BH4)2 and provides more hydrogen production sites for the hydrolysis reaction. At the same time, GO as a stable confined framework provides a favorable influence on regulating the hydrolysis rate.
[0044] Example 3
[0045] The method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material of this embodiment comprises the following steps:
[0046] First, 15 mg of GO was added to 20 mL of 2M (CH3)2S·BH3 toluene solution in an Ar-filled glove box, and the mixture was stirred for 15 min by a magnetic stirrer. Subsequently, 10 mL of 1M Mg(C4H9)2 heptane solution was slowly added to the GO / (CH3)2S·BH3 mixed solution through a pressure-separating funnel and stirred vigorously for 150 min. After the reaction was completed, it was washed five times with 13 mL of anhydrous toluene and the formed gray precipitate was collected. Finally, it was transferred to a vacuum drying oven and dried at 80 ° C for 14 h under 2 Torr vacuum.
[0047] The XRD spectrum of the hydrogen storage material prepared by the above method is as follows: Figure 1As shown, diffraction peaks corresponding to γ-Mg(BH4)2 appeared at 13.4°, 15.5°, 20.6°, 24.7°, etc. in the curve, indicating that the magnesium borohydride composite material was successfully synthesized by the intercalation-in situ growth method.
[0048] Figure 2 The hydrolysis kinetic curve of magnesium borohydride composite material at 25℃ is shown in Figure 2. Figure 2 It can be seen that 1g of powder can release 1030mL of hydrogen within 6min. Compared with γ-Mg(BH4)2, the hydrolysis reaction of MBH@15GO is more controllable and milder, the hydrolysis rate is slower, and it still has a higher hydrogen production.
[0049] Example 4
[0050] The method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material of this embodiment comprises the following steps:
[0051] First, 10 mg of MXene was added to 17 mL of 2M S(CH3)2·BH3 toluene solution in a glove box filled with Ar, and the mixture was stirred for 25 min by a magnetic stirrer. Subsequently, 10 mL of 1M Mg(C4H9)2 heptane solution was slowly added to the MXene / (CH3)2S·BH3 mixed solution through a pressure separator funnel and stirred vigorously for 150 min. After the reaction was completed, it was washed 4 times with 15 mL of anhydrous toluene and the formed gray precipitate was collected. Finally, it was transferred to a vacuum drying oven and dried at 80 ° C for 12 h under 4 Torr vacuum.
[0052] The XRD spectrum of the hydrogen storage material prepared by the above method is as follows: Figure 4 As shown, diffraction peaks corresponding to γ-Mg(BH4)2 appeared at 13.4°, 15.5°, 20.6°, 24.7°, etc. in the curve, indicating that the magnesium borohydride composite material was successfully synthesized by the intercalation-in situ growth method.
[0053] Figure 5 The hydrolysis kinetic curve of magnesium borohydride composite material at 25℃ is shown in Figure 2. Figure 5 It can be seen that 1g of powder can release 1004mL of hydrogen within 7min. Compared with γ-Mg(BH4)2, the hydrolysis reaction of MBH@10MX is more controllable and milder, the hydrolysis rate is slower, and it still has a higher hydrogen production.
[0054] Example 5
[0055] The method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material of this embodiment comprises the following steps:
[0056] First, 20 mg of MXene was added to 18 mL of 2M (CH3)2S·BH3 toluene solution in a glove box filled with Ar, and the mixture was stirred for 20 min by a magnetic stirrer. Subsequently, 10 mL of 1M Mg(C4H9)2 heptane solution was slowly added to the MXene / (CH3)2S·BH3 mixed solution through a pressure separator funnel and stirred vigorously for 140 min. After the reaction was completed, it was washed 5 times with 10 mL of anhydrous toluene and the formed gray precipitate was collected. Finally, it was transferred to a vacuum drying oven and dried at 85 ° C for 12 h under 2 Torr vacuum.
[0057] The XRD spectrum of the hydrogen storage material prepared by the above method is as follows: Figure 4 As shown, diffraction peaks corresponding to γ-Mg(BH4)2 appeared at 13.4°, 15.5°, 20.6°, 24.7°, etc. in the curve, indicating that the magnesium borohydride composite material was successfully synthesized by the intercalation-in situ growth method.
[0058] Figure 5 The hydrolysis kinetic curve of magnesium borohydride composite material at 25℃ is shown in Figure 2. Figure 5 It can be seen that 1g of powder can release 1312mL of hydrogen within 5.5min. Compared with γ-Mg(BH4)2, the hydrolysis reaction of MBH@20MX is more controllable and milder, the hydrolysis rate is slower, and it has a higher hydrogen production than γ-Mg(BH4)2.
[0059] from Figure 6 It can be seen that γ-Mg(BH4)2 is dispersed on the surface of MXene, which effectively avoids the aggregation problem in the process of synthesizing Mg(BH4)2 and provides more hydrogen production sites for the hydrolysis reaction. At the same time, MXene as a stable confined framework provides a favorable influence on regulating the hydrolysis rate.
[0060] Example 6
[0061] The method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material of this embodiment comprises the following steps:
[0062] First, 30 mg of MXene was added to 20 mL of 2M (CH3)2S·BH3 toluene solution in a glove box filled with Ar, and the mixture was stirred for 25 min by a magnetic stirrer. Subsequently, 10 mL of 1M Mg(C4H9)2 heptane solution was slowly added to the MXene / (CH3)2S·BH3 mixed solution through a pressure separator funnel and stirred vigorously for 140 min. After the reaction was completed, it was washed 4 times with 15 mL of anhydrous toluene and the formed gray precipitate was collected. Finally, it was transferred to a vacuum drying oven and dried at 80 ° C for 20 h under 3 Torr vacuum.
[0063] The XRD spectrum of the hydrogen storage material prepared by the above method is as follows: Figure 4 As shown, diffraction peaks corresponding to γ-Mg(BH4)2 appeared at 13.4°, 15.5°, 20.6°, 24.7°, etc. in the curve, indicating that the magnesium borohydride composite material was successfully synthesized by the intercalation-in situ growth method.
[0064] Figure 5 The hydrolysis kinetic curve of magnesium borohydride composite material at 25℃ is shown in Figure 2. Figure 5 It can be seen that 1g of powder can release 1249mL of hydrogen within 9.5min. Compared with γ-Mg(BH4)2, the hydrolysis reaction of MBH@30MX is more controllable and milder, the hydrolysis rate is slower, and it has a higher hydrogen production than γ-Mg(BH4)2.
[0065] It can be seen from Examples 1 to 6 that the hydrolysis rate and hydrogen production rate of hydrogen storage materials with different carriers and carrier addition amounts are different. Compared with the initial hydrogen release rate of γ-Mg(BH4)2 hydrolysis hydrogen production, which is too high and difficult to control, the initial hydrogen release rate of hydrogen storage materials with different carriers and carrier addition amounts is slow, easy to control, and the reaction conditions are mild. At some carrier addition amounts, it has a higher hydrogen production rate than γ-Mg(BH4)2 (see Figure 2 and Figure 5 ), which is more conducive to use in fuel cells.
[0066] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an in-situ generated magnesium borohydride composite hydrogen storage material, It is characterized in that The following steps are involved: S1. Add the support to (CH 3 ) 2 S.BH 3 In toluene solution, the mixture was stirred evenly to obtain suspension A; S2. Weigh the suspension A, Mg(C 4 H 9 ) 2 Heptane solution, stirring until complete reaction to obtain precipitate B, washing with anhydrous toluene solution and collecting precipitate B; S3. The precipitate B is transferred to a vacuum drying oven and thermally decomposed under vacuum conditions to obtain the in-situ generated magnesium borohydride composite hydrogen storage material.
2. The method for preparing the in-situ generated magnesium borohydride composite hydrogen storage material according to claim 1, Features: In step S1, the carrier is one or more of graphene, graphene oxide, MXene, silica, sepiolite, halloysite and montmorillonite.
3. The method for preparing the in-situ generated magnesium borohydride composite hydrogen storage material according to claim 1, Features: In step S1, the stirring time is 15 to 30 minutes.
4. The method for preparing the in-situ generated magnesium borohydride composite hydrogen storage material according to claim 1, Features: In step S1, the amount of carrier added is 3 to 50 mg, (CH 3 ) 2 S.BH 3 The concentration of the toluene solution is 1-2M.
5. The method for preparing the in-situ generated magnesium borohydride composite hydrogen storage material according to claim 1, Features: In step S2, the stirring time is 90 to 150 minutes.
6. The method for preparing the in-situ generated magnesium borohydride composite hydrogen storage material according to claim 1, Features: In step S2, Mg(C 4 H 9 ) 2 The concentration of heptane is 1-2M, (CH 3 ) 2 S.BH 3 Toluene solution and Mg(C 4 H 9 ) 2 The volume ratio of the heptane solution is (1.6-2):
1.
7. The method for preparing the in-situ generated magnesium borohydride composite hydrogen storage material according to claim 1, Features: In step S2, the volume of the anhydrous toluene solution is 10 to 15 mL, and the number of washing times is 3 to 5 times.
8. The method for preparing the in-situ generated magnesium borohydride composite hydrogen storage material according to claim 1, Features: In step S3, the thermal decomposition is carried out under vacuum conditions, wherein the vacuum pressure is 2-4 Torr, the heating temperature is 75-90° C., and the heating time is 8-20 hours.
9. An in-situ generated magnesium borohydride composite hydrogen storage material, It is characterized in that The preparation method is described in any one of claims 1 to 8.
10. Use of the in-situ generated magnesium borohydride composite hydrogen storage material prepared by the preparation method according to any one of claims 1 to 8 in producing hydrogen by hydrolysis.
Citation Information
Patent Citations
Hydroboron / graphdiyne composite hydrogen storage material as well as preparation method and application thereof
CN117550550A
Metal particles, useful for the hydrolysis reaction of a chemical hydride into hydrogen, comprises elements comprising group IIIA-VIIB of the periodic table of elements and their mixtures, carrying hydrophobic groups on their surface
FR2938456A1
A fast ionic conductor with stoichiometry mg(BH 4) 2·xnh 3
WO2020053423A1
